Adhesive Interactions of Leukocytes, Platelets, and the Vessel Wall during Hemostasis and Inflammation - McEver, Rodger P. (Thrombosis and Haemostasis, 2001)
In response to hemorrhage, circulating platelets adhere to exposed subendothelial tissues and then recruit additional platelets into aggregates that function as procoagulant surfaces. In response to inflammatory stimuli, circulating leukocytes roll and then arrest on endothelial cells, and finally migrate into the surrounding tissues where they combat pathogens and repair tissue injury. These traditionally separate cellular adhesive contributions to coagulation and inflammation have become progressively linked. We now know that leukocytes roll and then arrest on activated platelets and that platelets roll on activated endothelial cells. Cell adhesion molecules that were first thought to contribute uniquely to either coagulation or inflammation are now known to contribute to both responses. This review focuses on multicellular adhesive interactions in the vasculature, with particular attention to the dual functions of the adhesion molecules P-selectin, P-selectin glycoprotein ligand-1 (PSGL-1), and glycoprotein Ib (GPIb) in coagulation and inflammation.
Keywords: Selectin; integrin; PSGL-1; inflammation; hemostasis; cell adhesion; glycoprotein Ibα